Phase II trial of weekly erlotinib dosing to reduce duodenal polyp burden associated with familial adenomatous polyposis. Issue 2 (30th May 2022) - Samadder, N Jewel; Foster, Nathan; McMurray, Ryan P; Burke, Carol A; Stoffel, Elena; Kanth, Priyanka; Das, Rohit; Cruz-Correa, Marcia; Vilar, E; Mankaney, Gautam; Buttar, Navtej; Thirumurthi, Selvi; et al.
Abstract : Importance: Patients with familial adenomatous polyposis (FAP) are at markedly increased risk for duodenal adenomas and cancer. Combination sulindac and erlotinib was previously shown to reduce duodenal polyp burden but was associated with a relatively high adverse event (AE) rate. Objective: To evaluate if a once weekly dosing schedule for erlotinib intervention improves the AE profile, while still providing efficacy with respect to reduced polyp burden, in participants with FAP. Design, setting and participants: Single-arm trial, enrolling 46 participants with FAP, conducted from October 2017 to September 2019 in eight academic cancer centres. Exposures: Participants self-administered 350 mg of erlotinib by mouth, one time per week for 6 months. Main outcomes and measures: Duodenal polyp burden (sum of polyp diameters) was assessed in the proximal duodenum by esophagogastroduodenoscopy performed at baseline and 6 months, with mean per cent change defined as the primary efficacy outcome of interest. Rate of grade 2–3 AEs was evaluated as a co-primary outcome. Secondary outcomes included changes in total duodenal polyp count, along with changes in lower gastrointestinal (GI) polyp burden and count (for participants examined by optional lower endoscopy). Results: Forty-six participants (mean age, 44.1 years (range, 18–68); women, 22 (48%)) were enrolled; 42 participants completed 6 months of intervention and were included in the per-protocol analysis. Duodenal polyp burden was significantly reduced after 6 months of weekly erlotinib intervention, with a mean per cent change of −29.6% (95% CI, −39.6% to −19.7%; p<0.0001). Similar results were observed in subgroup analyses defined by participants with advanced duodenal polyposis (Spigelman 3) at baseline (mean, −27%; 95% CI, −38.7% to −15.2%; p<0.0001). Post-intervention Spigelman stage was downstaged in 12% of the participants. Lower GI polyp number was also decreased after 6 months of intervention (median, −30.8%; IQR, −47.4% to 0.0%; p=0.0256). Grade 2 or 3 AEs were reported in 71.7% of subjects, with only two experiencing grade 3 toxicity at least possibly related to intervention. Conclusion: In this single-arm, multi-centre trial of participants with FAP, erlotinib one time per week resulted in markedly lower duodenal polyp burden, and modestly reduced lower GI polyp burden, after 6 months of intervention. While AEs were still reported by nearly three-quarters of all participants, these events were generally lower grade and well-tolerated. These findings support further investigation of erlotinib as an effective, acceptable cancer preventive agent for FAP-associated GI polyposis. Trial registration number: NCT02961374 .